Self-Assemblies of Single-Walled Carbon Nanotubes through Tunable Tethering of Pyrenes by Dextrin for Rapidly Chiral Sensing. (28th July 2011) - Wei, Wei-Li; Chen, Qiushui; Li, Haifang; Lin, Jin-Ming
Abstract : Pyrene-modified dextrin (Py-Dex) was synthesized via the Schiff base reaction between reducing end of dextrins and 1-aminopyrene, and then self-assemblies of single-walled carbon nanotubes (SWNTs) were fabricated through the tunable tethering of pyrene to SWNTs by dextrin chains. The Py-Dex-SWNTs assemblies were found to be significantly water-soluble because of the synergistic effect of dextrin chains and pyrene moieties. Py-Dex and Py-Dex-SWNTs were adequately characterized by NMR, UV-vis, fluorescence spectroscopy, Raman spectroscopy, matrix-assisted laser desorption/ionization-time of flight mass spectroscopy, and transmission electron microscopy. The tethering effect of dextrin toward pyrene moieties was clearly revealed and was found to be tunable by adjusting the length of dextrin chains. The fluorescence of pyrene moieties was sufficiently quenched by SWNTs with the support of dextrin chains. Furthermore, the Py-Dex-SWNTs assemblies were used for chiral selective sensing by introducing cyclodextrins as chiral binding sites. The rapid chiral sensing was successfully tested for different enantiomers.